STUDI KEBERADAAN TERMINAL TIPE A PULAU TUJUH KABUPATEN MERANGIN JAMBI - Silviani, Febria - (Pendidikan Geografi, 2014)
This study aimed to obtain information, describe the existence of Terminal Study Type A Merangin District Seven Island seen from Jambi: 1) The cause is not the operation of the Terminal Type A Seven Island, 2) does not impact the operation of the Terminal Type A Seven Island, 3) solution or alternative troubleshooting Terminal type A Seven Island. This research is qualitative, the subject of this study is the Department of Transportation, Planning Office UPTD Terminal Type A Seven Island, PO driver, and communities around the Terminal Type A Seven Island were taken by purposive sampling (designated). Based on the findings in the field and interview the results of this study are as follows: (1) Cause of operation is not maximally Terminal Type A Merangin District Seven Island due to low accessibility is no public transportation leading to the terminal, the terminal facility is still incomplete still constrained water and still permissibility of bus fleets up and down the outside of the passenger terminal, thus appears terminal shadows, such as at the intersection of New Market and the edge of the Strip Three (Jatilur). (2) The impact due to the operation of the maximum Terminal Type A Merangin District Seven Island is for local government revenue is reduced and the driver income is lowered. So many of the drivers are available on the terminal shadow to look for passengers. (3) The solution or appropriate alternative solutions so that the Terminal Type A Seven Island Merangin District operates optimally is one of many efforts by the government to make public transportation route that leads to the terminal and crack down on bus fleets that do not open counters in the terminal and complete the infrastructure is not yet complete in the terminal to improve and optimize the Terminal type A Merangin District Seven Island.